Sampling design effects: do they affect the analyses of data from the National Survey of Families and Households? - Johnson, David R.; Elliott, Lisa A. (Journal of Marriage & Family, 1998)
The writers discuss whether sampling design effects influence the analyses of data from the National Survey of Families and Households (NSFH). They point out that most large national surveys involve clustered and stratified samples, and they contend that these complex sample designs have consequences for data analysis techniques. They assert that standard errors calculated using procedures that do not adjust for design effects are often too small and result in incorrect inferences. They examine design effects and estimate them for a set of variables selected from the 1988 NSFH. They present examples of descriptive estimates and regression results with household income and marital happiness as dependent variables. In addition, they consider statistical software that adjusts standard errors in complex designs, as well as issues relating to weighting and the analysis of subsamples.